2015
DOI: 10.1159/000369525
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke (AIS) Patient Management in French Stroke Units and Impact Estimation of Thrombolysis on Care Pathways and Associated Costs

Abstract: Background: Stroke is the second leading cause of death and a first leading cause of acquired disability in adults worldwide. This study aims to evaluate the current management and associated costs of acute ischemic stroke (AIS) for patients admitted in stroke units in France and over a one-year follow-up period as well as to assess the impact of improved thrombolytic management in terms of increasing the proportion of patients receiving thrombolysis and/or treated within 3 h from the onset of symptoms. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Stroke pathway effectiveness has also been explored previously, although some reported results have not been always statistically significant (Threlkeld et al, 2017;Schmidt et al, 2015;Willeit et al, 2015;Cloud et al, 2013;Taylor et al, 2006). Willeit et al (2015) demonstrated increased Stroke Unit access after implementing a comprehensive stroke management program, without changes in the mortality rate, though without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke pathway effectiveness has also been explored previously, although some reported results have not been always statistically significant (Threlkeld et al, 2017;Schmidt et al, 2015;Willeit et al, 2015;Cloud et al, 2013;Taylor et al, 2006). Willeit et al (2015) demonstrated increased Stroke Unit access after implementing a comprehensive stroke management program, without changes in the mortality rate, though without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence is available about clinical pathway implementation that targets acute ischemic stroke patients (Kim et al, 2014); however, implementation is associated with reduced stays (Fujino et al, 2014) and costs (Schmidt et al, 2015). Clinical pathway implementation for stroke patients has also been associated with reduced mortality (Willeit et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Senegal the cost of treatment is USD 416 (in 1997), while in Pakistan the cost is USD 5,230 (in 1998USD 5,230 (in -2001, the latter including only direct medical costs incurred during inpatient care (6). In high income countries the costs are even higher; in France, for example, the cost per patient episode (acute phase hospitalization) is estimated to be EUR 6 199.81 (in 2011) (7), while in Canada the cost sums up to USD 10544.45 (in 2008), including diagnostics, acute care services, rehabilitation, and surgical services during the inpatient stay (8). In the United States of America, the costs add up to USD 35,175 (in 2012), considering the hospital charges for the initial treatment of patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of all stroke cases receiving i.v. thrombolytic therapy was 18% in 2011 (4.9% in 2003) in Austria [ 13 , 14 ], and 16.7% in 2014-2015 in France [ 15 ], while this figure was only 3.2% in 2013 in Hungary, even though the number of thrombolysis procedures doubled between 2008 and 2013 [ 16 , 17 ]. The 3.2% thrombolysis rate was derived from 1,439 thrombolysis procedures performed at 37 active thrombolysis centers in 2013 across Hungary [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The organization of stroke centers required careful coordination in patient care with well-defined work flow and standard operating procedures [ 19 , 20 ]. As a result, our stroke center at the MUTH has been providing gradually improving acute stroke care, although still lagging behind that of Western European countries [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%